Genomic approaches for improving resistance to Phytophthora crown rot caused by P. cactorum in strawberry (Fragaria × ananassa) - Sharma, Sadikshya; Marin, Marcus V.; Lee, Man Bo; Baggio, Juliana S.; Peres, Natalia A.; Lee, Seonghee (Frontiers in Agronomy, 2022)
Phytophthora crown rot (PhCR) caused by Phytophthora cactorum is one of the most damaging soilborne diseases of strawberry in the U.S. and worldwide. Limitations on fumigants such as methyl bromide have led to deterioration in the control of P. cactorum in recent years. The development of resistant varieties is a critical component of the strategy for combatting this soil-borne disease. Here, we review the biology of the pathogen, molecular mechanisms of infection and management of PhCR in strawberry. Recent genomics advances in octoploid strawberry breeding have been able to gain a deeper insight into the genetic architecture of resistance to PhCR and identified the genetic resistance sources for the improvement of strawberry varieties against the pathogen. Quantitative trait loci (QTL) associated with PhCR resistance have been identified and introgressed for breeding of PhCR resistance in cultivated octoploid strawberry (F. ×ananassa). Further characterizing candidate genes and mechanisms of resistance could facilitate incorporating the resistance genes into commercial varieties through genomics-assisted breeding, respectively. In this review, we address important recent advances and progress for genomics-assisted breeding for the resistance to PhCR and the potential use of CRISPR gene editing in cultivated strawberry.